Comparison and performance analysis of some active vibration control algorithms. (January 2014) - Orivuori, Juha; Zenger, Kai
In this paper, a survey comparing some of the present linear control algorithms for the active control of sinusoidal tonal disturbances is made. The design procedure for each of the methods is presented in detail and the similarities in the design are pointed out. The methods are studied in a common framework in order to allow analytical comparison. The focus of the analysis is in the best obtainable control performance in terms of the vibration mitigation, the controller robustness and the sensitivity to process noise and model errors. In addition, some issues related to the transient behavior of the algorithms, such as the convergence rate, are evaluated in time-domain simulations . The purpose of this study is to establish a clear view on the differences and similarities between the present algorithms and to provide some insight for a system specialist, on how to choose an appropriate control algorithm for a particular problem. It will be shown that the choice for an appropriate algorithm is problem dependent.